High-Mobility Group Box-1 Protein Serum Levels Do Not Reflect Monocytic Function in Patients with Sepsis-Induced Immunosuppression - Nadine Unterwalder; Christian Meisel; Konstantinos Savvatis; Ben Hammoud; Christina Fotopoulou; Hans-Dieter Volk; Petra Reinke; Joerg C. Schefold (Mediators of Inflammation)
Background. High-mobility group box-1 (HMGB-1) protein is released during “late sepsis” by activated monocytes. We investigated whether systemic HMGB-1 levels are associated with indices of monocytic activation/function in patients with sepsis-induced immunosuppression. Methodology. 36 patients (31 male, 64±14 years) with severe sepsis/septic shock and monocytic deactivation (reduced mHLA-DR expression and TNF-α release) were assessed in a subanalysis of a placebo-controlled immunostimulatory trial using GM-CSF. HMGB-1 levels were assessed over a 9-day treatment interval. Data were compared to standardized biomarkers of monocytic immunity (mHLA-DR expression, TNF-α release). Principle findings. HMGB-1 levels were enhanced in sepsis but did not differ between treatment and placebo groups at baseline (14.6 ± 13.5 versus 12.5 ± 11.5 ng/ml, P=.62). When compared to controls, HMGB-1 level increased transiently in treated patients at day 5 (27.8±21.7 versus 11.0±14.9, P=.01). Between group differences were not noted at any other point of assessment. HMGB-1 levels were not associated with markers of monocytic function or clinical disease severity. Conclusions. GM-CSF treatment for sepsis-induced immunosuppression induces a moderate but only transient increase in systemic HMGB-1 levels. HMGB-1 levels should not be used for monitoring of monocytic function in immunostimulatory trials as they do not adequately portray contemporary changes in monocytic immunity.